The aesthetics of the title in the collection (Tigers on the Tenth Day) by Zakaria Tamer (Damascus University Journal of arts and humanities sciences, 2026)
Studies of textual thresholds have recently gained increasing attention, particularly the title, as a textual structure that interweaves with other textual structures in a dialectical relationship aimed at achieving communication between the creator and the recipient through its various functions, particularly aesthetic ones. The title is a linguistic structure that, in its condensed form, possesses expressive potential that opens up to the text, interacting with it at various levels, contributing to the production of its meanings and connotations in each new reading.Zakaria Tamer is a unique short story writer with a unique narrative text that has become, in his poetics, a poem that encourages exploratory reading, in which the title becomes a procedural key to unlocking the mysteries of the text and exploring its semantic and symbolic depths. The collection “Tigers on the Tenth Day” constitutes the centerpiece of Zakaria Tamer’s creative narratives; therefore, it was chosen as the subject of the study. In order to approach the titles in their structure andtheir relationships with their texts and with other texts outside their texts, the research adopted the semiotic approach in description and analysis, and arrived at a set of results, the most prominent of which are:Zakaria Tamer bases his titles on a clear intention, but he always succeeds in obfuscating and concealing his intention, so that the reader enters into the adventure of interpretation and the search for meaning, which gives his titles a unique aesthetic. The choice of “Tigers on the Tenth Day” as the title of the collection “confirms the importance of the story as a title and a text in comparison to other stories with their titles and texts on the one hand, and the short story writer’s skill in creating a title that achieves the dialectic of extension in his text and the recoil from it on the other hand.”
Keywords: Title; Parallel Text; Tigers on the Tenth Day; Zakaria Tamer